Museum Smend marketing strategy in increasing tourist visits - Lailatul, Fatimah Nurul; Nugraha, Julyan Tama; Hariyanti, Nunik (COMMICAST, 2021)
Nusantara batik is a traditional work of art that has certain motifs originating from regions throughout Indonesia. Indonesian batik has unique motifs so that many foreigners love Indonesian batik. Germany is one country that really admires the work of Indonesian batik. One proof of this is the establishment of the Smend Batik Museum which is located in the center of Cologne City, to be precise in the Mainzerstra area. â€E. The Batik Smend Museum has a marketing strategy to attract readers and tourists to visit the Smend Batik Museum. This study aims to see the marketing strategy used by the Museum Batik Smend in increasing foreign tourist visits. The research method used is a literature study with a qualitative approach. The results showed that the website media can increase foreign tourist visits.